Administrative Capacity in the Implementation of Local Government Grants for Early Childhood Education: A Literature Review - Puspa Ayu Widhi Pangestu; Priyanto Priyanto; Ulul Albab; Sri Kamariyah (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
This article examines administrative capacity at the local government level as a critical determinant of the effective implementation of grants for Early Childhood Education (ECE), a policy domain widely recognized as a strategic public investment with long-term social and economic returns. Despite the growing reliance on subnational grants to finance ECE services across diverse governance systems, implementation outcomes remain uneven, frequently constrained by limited administrative capacity, weak public financial management, fragmented governance arrangements, and fragile accountability mechanisms. Responding to these challenges, this study aims to synthesize and critically assess the international literature to clarify how administrative capacity shapes the design–implementation nexus of local government ECE grants and to identify the institutional, managerial, and fiscal conditions under which such grants are more likely to achieve their intended objectives. Methodologically, the article adopts a conceptual–comparative literature review approach, drawing on a systematic search of peer-reviewed journal articles from major academic databases and applying thematic synthesis to integrate findings across governance contexts and policy traditions. The review is anchored in Administrative Capacity Theory and analytically enriched through insights from policy implementation theory, public financial management, good governance, and public accountability. The synthesized findings demonstrate that administrative capacity operates as a multidimensional and relational construct, encompassing institutional coherence, managerial coordination, human resource competence, procedural stability, and analytical capability. The literature consistently shows that weaknesses across these dimensions undermine grant implementation through delays, inefficiencies, limited oversight, and uneven service quality, while strong capacity enables more predictable, accountable, and effective ECE grant governance.